Kidnapping for rituals in Nigeria - Oyewole, Samuel (The political economy of kidnapping and insecurity in Nigeria, 2024)
Ritual motivated kidnapping is one of the most alarming criminal violence that underscored the underworld political economy of Nigeria. The beliefs in traditional, religious and superstitious power of human spirit, blood, body and/or body parts (exhumed from grave or purposively killed/murdered) to advance materialist interests such as fame, favour, power, protection, success and wealth have inspired a growing trend of kidnapping for this purpose in Nigeria and beyond. Nevertheless, this phenomenon has remained one of the least publicised, researched and understood criminal activities. This chapter examines the nature of kidnapping for ritual in Nigeria. In this process, attention is given to the evolution of this threat, it spread and concentration, actors that are involved, frequently targeted victims, strategies employed and the implications for security.